Complement and Coagulation Cascade Activation Regulates the Early Inflammatory Mechanism of Resistance of Suckling Lambs Against Haemonchus contortus - Lins, José Gabriel G. [UNESP]; Amarante, Alessandro F. T. [UNESP] (MDPI, 2025)
Haemonchus contortus is a highly pathogenic blood-sucking nematode from the abomasum of small ruminants. To develop effective control strategies, it is essential to understand the initial mechanisms involved in host resistance to this parasite. In this study, we used computational tools to analyze the complement and coagulation pathways generated from RNA sequencing of abomasal tissue from resistant (Santa Ines) and susceptible (Ile de France) young sheep artificially infected with H. contortus. Thirty-two differentially expressed genes annotated to the ovine genome were associated with the complement and coagulation cascades, of which 29 of them were overexpressed in Santa Ines. Our data identified potential markers for resistance trait selection in sheep, such as C3 (complement C3), F3 (tissue factor), F5 (coagulation factor V), CFB (complement factor B), and CFI (complement factor I). Santa Ines may have a more robust coagulation system, being activated by extrinsic pathways associated with tissue damage. The complement may act as a mediator of the innate immunity, and its activation in Santa Ines is associated with the classical, the lectin, and the alternative pathway. Finally, resistant Santa Ines lambs had a polygenic overexpressed architecture controlling both complement and coagulation cascades, which probably contributed to the early-onset protection against H. contortus.